BEBERAPA TEOREMA TITIK TETAP UNTUK PEMETAAN KONTINU DI RUANG METRIK KOMPAK - Ahmad Khairul Umam; Ahmad Isro'il; Pukky Tetralian B. N. (Jurnal Matematika dan Sains (JMS), 2021)
The fixed point principle is very important in solving linear equation, ordinary differential equation, partial differential equation, and integral equation. The famous fixed point theorem is Banach's fixed point theorem. Kannan's fixed point theorem is generalisation of Banach's fixed point theorem. This article discusses some theorems that generalisations from Kannan's fixed point theorem with continuity mapping. Some theorems are discussed in this article guarantee the existence and uniqueness of a fixed point.